Seroprevalence of antibodies of Neospora spp. and Toxoplasma gondii in horses from southern Italy - Bartova, Eva; Machacova, Tereza; Sedlak, Kamil; Budikova, Marie; Mariani, Ugo; Veneziano, Vincenzo (Folia parasitologica, 2015)
The consumption of horse meat has been epidemiologically linked to clinical toxoplasmosis in humans and neosporosis that may cause clinical illness in horses. Here we determined seroprevalence of antibodies against Toxoplasma gondii Nicolle et Manceaux, 1908 and species of Neospora Dubey, Carpenter, Speer, Topper et Uggla, 1988 in horses from Italy. Blood samples were collected from 643 apparently healthy horses from 60 farms of 51 municipalities in southern Italy. The presence of antibodies against T. gondii and Neospora spp. were detected by indirect fluorescence antibody test (IFAT); a titre ≥ 50 was considered positive. The same sera were also tested for antibodies against Neospora spp. by a competitive-inhibition enzyme-linked immunosorbent assay (cELISA); samples with ≥ 30% inhibition were considered positive. Antibodies against T. gondii and Neospora spp. were detected in 19 (3.0%) and 15 (2.3%) horses by IFAT, respectively, without statistical difference between gender, age and breeds (p-value ≥ 0.05). Antibodies against species of Neospora were detected in 70 (10.9%) horses by cELISA with statistical difference in gender (6.0-18.5%, p-value ≥ 0.05) and breeds (0-19.4%, p-value ≥ 0.05). Although T. gondii infection rates were low, the risk of human infection should not be dismissed, particularly in Italy where consumption of raw or undercooked horse meat has a long tradition.
Keywords: risk factor; Equus caballus; serological test; neosporosis; toxoplasmosis